Physics of semiconductor devices : IWPSD, 2003 : proceedings of the Twelfth International Workshop on the Physics of Semiconductor Devices - International Workshop on the Physics of Semiconductor Devices 2003 : IIT, Madras); Bhat, K. N.; DasGupta, A. (Amitava) (New Delhi : Narosa Pub. House, 2004)
Contributed papers of the workshop held at IIT, Madras, in 2003
Includes bibliographical references and index
Keywords: Semiconductors -- Congresses